2017
DOI: 10.1016/j.neulet.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Plasma neurofilament light chain levels in Alzheimer’s disease

Abstract: Plasma neurofilament light (NFL) levels may be a marker of neuronal injury. We examined whether plasma NFL might be a potential biomarker for the prodromal and dementia stages of AD. Participants included 193 cognitively normal (CN), 198 amnestic mild cognitive impairment (aMCI) and 187 Alzheimer's disease (AD) individuals enrolled in the Alzheimer's Disease Neuroimaging Initiative (ADNI). Plasma NFL levels were examined by the Single Molecule array (Simoa) technique. Our results showed significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
74
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 16 publications
17
74
3
Order By: Relevance
“…In AD, plasma or serum levels of NF-L have been shown to be elevated compared with controls in presymptomatic individuals known to be carriers of AD-causing gene mutations [385] and subjects with MCI or AD [240, 408]. Furthermore, blood-based NF-L appears to correlate with poor cognition and brain atrophy [240, 385].…”
Section: Other Neuronal Proteinsmentioning
confidence: 99%
“…In AD, plasma or serum levels of NF-L have been shown to be elevated compared with controls in presymptomatic individuals known to be carriers of AD-causing gene mutations [385] and subjects with MCI or AD [240, 408]. Furthermore, blood-based NF-L appears to correlate with poor cognition and brain atrophy [240, 385].…”
Section: Other Neuronal Proteinsmentioning
confidence: 99%
“…Twelve studies compared blood (i.e., plasma and serum) NfL concentration in AD cases and cognitively unimpaired controls [4,9,25,30,42,[47][48][49][50][51][52][53]; however, three of these studies used largely overlapping data from the ADNI database [49,50,53]. To avoid bias, the largest of the three overlapping studies was selected for inclusion in the meta-analysis [53]; thus, 10 studies comparing 471 AD cases to 518 cognitively unimpaired controls were included in the meta-analysis. The average AD to control blood NfL concentration ratio was 2.61 (95% CI 1.54-4.44, P 5 0.003; Fig.…”
Section: Nfl In Admentioning
confidence: 99%
“…2D). Of these studies, 5 studies (365 AD cases and 357 cognitively unimpaired controls) compared NfL concentration in plasma, with an average ratio of 2.11 (95% CI 0.78-5.73) [25,30,47,48,53]. The remaining 5 studies (106 AD cases and 161 cognitively unimpaired controls) compared serum NfL concentration [4,9,42,51,52], with an average ratio of 3.22 (95% CI 1.37-7.57).…”
Section: Nfl In Admentioning
confidence: 99%
“…The most recent studies using single molecule array (Simoa) technique for NFL determination have shown significantly higher serum NFL levels in the AD group even in prodromal stadium compared to normal controls. However the overlap between the AD and other diagnostic groups was obvious 14,15 . Despite this limitation plasma NFL levels may be a useful noninvasive biomarker of neurodegenerative processes 15 .…”
Section: Discussionmentioning
confidence: 95%
“…Correlation of CSF NFL with accelerated cognitive decline, changes in white matter and increased brain atrophy is found in patients with mild cognitive impairment 12 . Recently, elevated NFL levels were also described in the serum/plasma of AD patients [13][14][15] . NFH elevation in CSF seems to be less prominent in AD.…”
Section: Introductionmentioning
confidence: 97%